2001
DOI: 10.1287/trsc.35.4.375.10432
|View full text |Cite
|
Sign up to set email alerts
|

Benders Decomposition for Simultaneous Aircraft Routing and Crew Scheduling

Abstract: G iven a set of flight legs to be flown by a single type of aircraft, the simultaneous aircraft routing and crew scheduling problem consists of determining a minimum-cost set of aircraft routes and crew pairings such that each flight leg is covered by one aircraft and one crew, and side constraints are satisfied. While some side constraints such as maximum flight time and maintenance requirements involve only crews or aircraft, linking constraints impose minimum connection times for crews that depend on aircra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
151
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(161 citation statements)
references
References 24 publications
1
151
0
1
Order By: Relevance
“…Geoffrion and Graves (1974) confirmed that the method is suitable to solve large scale multicommodity distribution system design models. Many other applications of Benders decomposition have been proposed since then (see, for example, Richardson 1976;Magnanti et al 1986;Cordeau et al 2000;Cordeau et al 2001). Methodologies for improving the performance of the method have been proposed in McDaniel and Devine (1977) and Magnanti and Wong (1981).…”
Section: A Benders Decomposition Approachmentioning
confidence: 99%
“…Geoffrion and Graves (1974) confirmed that the method is suitable to solve large scale multicommodity distribution system design models. Many other applications of Benders decomposition have been proposed since then (see, for example, Richardson 1976;Magnanti et al 1986;Cordeau et al 2000;Cordeau et al 2001). Methodologies for improving the performance of the method have been proposed in McDaniel and Devine (1977) and Magnanti and Wong (1981).…”
Section: A Benders Decomposition Approachmentioning
confidence: 99%
“…For routing and scheduling problems arising in areas such as airline planning, Benders' decomposition together with column generation has successfully been applied by Cordeau et al in [6] to simultaneously consider both the aircraft routing problem and the crew pairing problem something that traditionally have been done sequentially due to the large complexity of the problem. Their implementation rst uses a linear programming (LP) relaxation of both Benders master problem and Benders subproblem, and later reintroduces the integer requirements and performs a heuristic branching on the integer variables.…”
Section: Benders' Decompositionmentioning
confidence: 99%
“…The altered image in Figure 1 is thus available under the same license. 6 to more satis ed customers. This type of optimization tool can also help Volvo to better understand their customers' needs, which may then in uence strategic vehicle development decisions and make Volvo even more competitive on the tough global vehicle market.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations